AKTIVITAS ANTIOKSIDAN DAN IDENTIFIKASI SENYAWA EKSTRAK JAMUR LINGZHI (Ganoderma lucidum) DENGAN LIQUID CHROMATOGRAPHY-MASS SPECTROMETRY (LC-MS) - Farida Nuraeni; Septi Bernadetha Br Sembiring (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2019)
Lingzhi mushroom is widely used as an alternative treatment to reduce blood pressure and blood sugar levels, to maximize the potential of the Lingzhi fungus antioxidant tests are carried out. This study aims to determine the potential antioxidant activity of water extract and 70% ethanol extract of Lingzhi mushroom with maceration extraction time variation and identification of compounds with Liquid Chromatography Mass Spectrometry (LC-MS). This research begins with the determination of fresh lingzhi mushrooms then made simplicia and extracted by maceration with time variation with soaking time of 24 hours, 48 hours and 72 hours each with 2 solvents namely water and 70% ethanol. The extract was tested by phytochemistry followed by testing the antioxidant activity of Lingzhi mushroom extract (ganoderma lucidum) by DPPH method. Then the compounds were identified by Liquid Chromatography-Mass Spectrometry (LC-MS). Based on the results of research that maceration for 1 hour (1 day) Lingzhi mushroom with 70% ethanol extraction has the potential as an antioxidant with an IC50 value of 94.83 ppm. The results of identification with LC-MS in 70% ethanol extract as a compound that has potential as an antioxidant are Bisphenol M compounds, and 1- - [[2- (3,4-Dimethoxyphenyl) amino]} -3-methyl-2-octylpyrido [1 , 2-a] benzimidazole-4-carbonitrile.